PEDAGOGICAL FUNDAMENTALS OF DEVELOPMENT OF CONTINUOUS EDUCATION (Archive of Conferences, 2021)
The article analyzes the organizational, legal, modern pedagogical bases of the development of the system of continuing education in Uzbekistan.